Cover, Content, and Editorial Note from J Mol Docking Vol. 1 No. 1 June 2021 - Chief Editor of J Mol Docking (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Assalamu’alaikum Wr. Wb.Alhamdulillahirabbil ‘alamin. After a long wait for almost 1 year from the first planned, finally, the new scientific journal of the Department of Pharmacy Universitas Muhammadiyah Palangkaraya can be published. This scientific journal was named the Journal of Molecular Docking (J Mol Docking), inspired by one of the most popular in silico methods in computer-aided drug design. Journal of Molecular Docking published every 6 months (2 issues/year) every June and December.This edition contains five articles consisting of writings from four countries including Indonesia, India, Bulgaria, and Egypt. The authors come from several institutions, including Bio Search Research Institution, Sekolah Tinggi Farmasi Muhammadiyah Tangerang, Sri Ramachandra Institute of Higher Education and Research, Siddha Central Research Institute – Central Council for Research in Siddha, Chhattisgarh Swami Vivekanand Technical University, Universitas Mataram, and Medical University – Sofia.Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for publication in the next edition in December 2021.Wassalamu’alaikum Wr. Wb.